Evaluation of stable and non shattering isabgol cultivar - Gujarat isabgol 4 - H Patel, A U Amin, D G Patel, H B Patel, P T Patel, (Journal of Spices and Aromatic Crops, 2018)
Isabgol growing area was surveyed during 2009-10 and selected genotypes were evaluated in preliminary evaluation trial (PET) during 2010-13 and in large scale varietal trial (LSVT) during 2013-15. It was found that JI-09-21 recorded better growth and yield characters and yield over check Gujarat Isabgol 3. The JI-09-21 did not shatter much even after water dripping and recommended for cultivation as Gujarat Isabgol 4.